2023
DOI: 10.1001/jamanetworkopen.2023.38182
|View full text |Cite
|
Sign up to set email alerts
|

The Patient Experience of Prior Authorization for Cancer Care

Fumiko Chino,
Alexandra Baez,
Ivy B. Elkins
et al.

Abstract: ImportancePrior authorization (PA) requires clinicians and patients to navigate a complex approval pathway. Resultant delays and denials can be particularly problematic for patients with cancer, who often need urgent treatment or symptom management.ObjectiveTo investigate the patient perspective of PA for cancer-related care, including perceptions about the process, outcomes (including delays and denials), and patient administrative burden.Design, Setting, and ParticipantsThis cross-sectional, anonymous survey… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Studies in other cancers have similarly found low correspondence between FDA approvals and patient receipt of medication and high approval rates after prior authorization ( Dickens and Pollock, 2017 , Tran et al, 2019 ) Yet each prior authorization request adds 30–60 min on average to clinical staff workload ( Dickens and Pollock, 2017 , Niccolai et al, 2017 ). A 10-day delay from PARP inhibitor prescription to patient receipt after prior authorization may not have a clinical impact on cancer recurrence, but it creates anxiety and work for patients and clinicians ( Chino et al, 2023 ). Early prescription of PARP inhibitor, such as with cycle 5–6 of chemotherapy, may reduce time from chemotherapy end to PARP inhibitor start.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in other cancers have similarly found low correspondence between FDA approvals and patient receipt of medication and high approval rates after prior authorization ( Dickens and Pollock, 2017 , Tran et al, 2019 ) Yet each prior authorization request adds 30–60 min on average to clinical staff workload ( Dickens and Pollock, 2017 , Niccolai et al, 2017 ). A 10-day delay from PARP inhibitor prescription to patient receipt after prior authorization may not have a clinical impact on cancer recurrence, but it creates anxiety and work for patients and clinicians ( Chino et al, 2023 ). Early prescription of PARP inhibitor, such as with cycle 5–6 of chemotherapy, may reduce time from chemotherapy end to PARP inhibitor start.…”
Section: Discussionmentioning
confidence: 99%
“…[44][45][46] National estimates of the time spent receiving health care are highest among adults newly diagnosed with cancer, although time spent related to health care remains elevated throughout survivorship. 45,46 Emerging research suggests that patients spend significant time with administrative tasks related to their health care, including addressing issues with health insurance coverage (e.g., prior authorizations for treatment) 47 and contesting medical bills, 48 which also must often take place during work hours. Time spent receiving health care has long been recognized as having an economic cost (i.e., patient time costs); more recently, this concept has been denoted as time toxicity to reflect the time burden of intensive care.…”
Section: Is Paid Sick Leave Sufficient For the Amount Of Time Require...mentioning
confidence: 99%
“…14,15 In a cross-sectional survey, 22% of cancer patients reported that they did not receive care as originally recommended by their oncologists. 16 At 97% of services, radiation oncology has been reported to be the medical specialty with the highest proportion of services for which insurers require authorization prior to treatment. 2 One academic radiation oncology practice estimated its annual prior authorization-related cost burden to be nearly $500,000.…”
Section: Introductionmentioning
confidence: 99%